2022
DOI: 10.1111/eci.13773
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malignancy on outcomes in European patients with atrial fibrillation: A report from the ESC‐EHRA EURObservational research programme in atrial fibrillation general long‐term registry

Abstract: Background:The management of patients with atrial fibrillation (AF) and malignancy is challenging given the paucity of evidence supporting their appropriate clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…By combining these clinical events, NACE offers a more comprehensive evaluation of the risk–benefit profile of anticoagulation therapy and is therefore used in major clinical trials, particularly those seeking a balance between efficacy and bleeding risk [ 32 , 33 ]. We developed a multivariable model that incorporates known risk factors (components of the CHA 2 DS 2 -VASc score) and new risk factors (malignancy, left atrial size, and left ventricular ejection fraction) that have been evaluated in previous studies [ 34 , 35 ]. By employing suitable primary outcomes and multivariable modelling, our study offers insightful guidance on the application of anticoagulation therapy for patients with advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…By combining these clinical events, NACE offers a more comprehensive evaluation of the risk–benefit profile of anticoagulation therapy and is therefore used in major clinical trials, particularly those seeking a balance between efficacy and bleeding risk [ 32 , 33 ]. We developed a multivariable model that incorporates known risk factors (components of the CHA 2 DS 2 -VASc score) and new risk factors (malignancy, left atrial size, and left ventricular ejection fraction) that have been evaluated in previous studies [ 34 , 35 ]. By employing suitable primary outcomes and multivariable modelling, our study offers insightful guidance on the application of anticoagulation therapy for patients with advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DOACs constitute a group of drugs that overtake traditional VKAs in anticoagulation treatment [45][46][47]. Papers provide evidence of DOACs' benefits compared to traditional therapy with VKAs [48][49][50][51][52][53][54]. In cancer patients, VKA use was associated with a higher risk of cancer-associated thrombosis (CAT) and recurrence of bleeding compared with the general population [55,56].…”
Section: Doacs' Potential To Replace Classical Vkas In the Therapy Of...mentioning
confidence: 99%
“…Similarly, several studies pointed out that cancer survivors are at higher risk of developing coronary artery disease (CAD), valvular heart disease (VHD), and heart failure (HF) at long-term follow-up [3,4]. Physicians will have to manage an increasing number of cancer patients presenting with chronic and acute CVDs in the near future [5][6][7]. In this context, an integrated and personalized approach to patient care, relying on multidisciplinary teams including cardiologists and oncologists, is gaining actual relevance [8][9][10], even in the peculiar setting of emergency departments (EDs) [11,12].…”
Section: Introductionmentioning
confidence: 99%